Sexual dysfunctions among people living with aids in Brazil (Clinics, 2010)
INTRODUCTION: Sexual dysfunction symptoms in patients with HIV have not been fully investigated in Brazil. OBJECTIVES: To investigate the association between sexual dysfunction symptoms and AIDS among participants in the Brazilian Sex Life Study. METHODS: The Brazilian Sex Life Study is a cross-sectional population study. The participants answered an anonymous self-responsive inquiry. It was applied to a population sample in 18 large Brazilian cities. Answers given by those who reported having AIDS (75) were compared with those who reported not having AIDS (control; 150). This was a case-control study nested in a cross-sectional population study. RESULTS: In females, AIDS was associated with "sexual inactivity over the last 12 months" and "does not maintain sexual arousal until the end of the sex act" (P < 0.05) after adjusting for race and thyroid disease. Compared to the control group, men with AIDS had more difficulty becoming sexually aroused (they required more help from their partner to begin the sex act, they required longer foreplay than they wished, they reported losing sexual desire before the end of the sex act, and they required longer to ejaculate than they desired) (P < 0.05). After adjusting for sexual orientation, sex hormone deficiency, depression, and alcoholism, only "does not have sexual desire," "have longer foreplay," and dyspareunia were associated with AIDS. DISCUSSION AND CONCLUSIONS: The results support the hypothesis that sexual dysfunctions are associated with AIDS. Men with AIDS need more time and stimulation to develop a sexual response, and a significant portion (37%) of women with AIDS reported sexual inactivity over the last 12 months.